Investigation of new products of quercetin formed in boiling water via UPLC-Q-TOF-MS-MS analysis. (30th August 2022) - Lin, Shiye; Zhang, Haolin; Simal-Gandara, Jesus; Cheng, Ka-Wing; Wang, Mingfu; Cao, Hui; Xiao, Jianbo
Graphic abstract: Quercetin tends to be degraded in boiling water to produce phenolic acids and other new products via oxidation, hydroxylation and nucleophilic attack cleavage. Highlights: The stability of quercetin in boiling water was investigated. Quercetin was instable in boiling water and formed various degraded products. The main new products were 3, 4-dihydroxybenzoic acid and 2, 4, 6-trihydroxybenzoic acid. Abstract: Quercetin is one of most important flavonoids in foods with multi-benefits for human health. The thermal processing is the main food processing approach. Here, the stability of quercetin in boiling water (100 °C) was investigated by UPLC-Q-TOF-MS-MS. With the increasing boiling time, quercetin gradually degraded, and the initial degradation time is 17.57 min and the half-degradation time is 169.72 min. The degradation mechanisms included oxidation, hydroxylation and nucleophilic attack cleavage. Combining the retention time and characteristic fragment ion information of the corresponding standards, the degraded products of quercetin in boiling water were identified as 3, 4-dihydroxyphenylglyoxylate, 1, 3, 5-trihydroxybenzene, 3, 4, 5-trihydroxybenzoic acid and 2, 4, 6-trihydroxybenzoic acid. Moreover, 2, 3-dihydro-2, 3′, 4′, 5, 7-pentahydroxy-3-oxoflavone, quercetin dimers and quinones were also formed.